Simple centromere, complex kinetochore: linking spindle microtubules and centromeric DNA in budding yeast - Cheeseman, Iain M. (The Rockefeller University Press, 2002)
Although the budding yeast centromere is extremely short (125 bp) compared to those of other eukaryotes, the kinetochore that assembles on this DNA displays a rich molecular complexity. Here, we describe recent advances in our understanding of kinetochore function in budding yeast and present a model describing the attachment that is formed between spindle microtubules and centromeric DNA. This analysis may provide general principles for kinetochore function and regulation.